No one listens to us, we know this, so we participated: Qualitative evidence from menstruation research during the COVID-19 pandemic - Eleanor J Junkins; Samar Chehab; Katharine MN Lee; Kathryn BH Clancy (Women's Health)
Background: We created a survey to assess menstrual side effects after COVID-19 vaccination when we noticed news stories that denied or discounted the experiences of tens of thousands of menstruating and formerly menstruating people who reported experiencing bleeding changes. This survey had an unprecedented response hundreds of times higher than we had anticipated ( n  = 101,824). Objectives: We investigated what motivated our sample to participate without remuneration to understand both general motivations for survey participation as well as why this survey captured the interest of so many. Design: We used open-ended responses from our online, mixed-method survey collected from April to October 2021. Methods: Using computer-assisted qualitative data analysis tools in R, we conducted a thematic analysis on open-ended responses. We used topic modeling to cluster the data, synthesize responses across 22,737 participants, and inform the themes summarizing the responses to “What is your interest in this project?” We compared and contrasted responses across groups (racial identity, ethnicity, gender) to examine whether the themes were representative across the demographic groups in our study. Results: The themes that characterized participants’ interest in participating were vaccine effects and women’s/people’s health, personal experience related to the vaccine, and a love for science and data. We compared responses among demographic subgroups to avoid an overfocus on majority group responses and found the themes were reflected across each group. Lastly, we found our themes reflected multiple types of altruism. Conclusion: These results were important in showing how emergent research that focuses on the concerns of potential participants can encourage high response rates from both marginalized and majority communities. Inclusive practices and familiarity with the research team built credibility that engendered trust with the public.